2019
DOI: 10.3390/ijms20122937
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: A Potential Mechanism Involved in the Pathogenesis of Various Adverse Consequences of Obstructive Sleep Apnea

Abstract: Epigenetics is defined as the heritable phenotypic changes which do not involve alterations in the DNA sequence, including histone modifications, non-coding RNAs, and DNA methylation. Recently, much attention has been paid to the role of hypoxia-mediated epigenetic regulation in cancer, pulmonary hypertension, adaptation to high altitude, and cardiorenal disease. In contrast to sustained hypoxia, chronic intermittent hypoxia with re-oxygenation (IHR) plays a major role in the pathogenesis of various adverse co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 93 publications
(102 reference statements)
0
22
0
1
Order By: Relevance
“…Consequently, the patient generally presents fatigue, excessive daytime sleepiness, morning headache, attention or memory impairment, and habitual snoring history, and carries increased risks of hypertension, ischemic heart disease, diabetes mellitus, and cognitive dysfunction. Recent randomized controlled trials have not demonstrated significant protective effects of long-term continuous positive airway pressure treatment on cardiovascular events or mortality, indicating the need of developing pharmaceutical agents to improve outcomes in OSA patients [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the patient generally presents fatigue, excessive daytime sleepiness, morning headache, attention or memory impairment, and habitual snoring history, and carries increased risks of hypertension, ischemic heart disease, diabetes mellitus, and cognitive dysfunction. Recent randomized controlled trials have not demonstrated significant protective effects of long-term continuous positive airway pressure treatment on cardiovascular events or mortality, indicating the need of developing pharmaceutical agents to improve outcomes in OSA patients [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated a pivotal role of H3K4me3 and H3K9me3 over the promoter regions in epigenetic activation of the NOX-1, -2, -4, and -5 genes for cellular senescence and endothelial dysfunction [59,60]. Recently, it was suggested that sustained hypoxia can upregulate the oxygen-dependent demethylases (KDMs), which may increase demethylation of methylated lysine residues, including H3K9me3 and H3K4me3 [2,[61][62][63]. Another study showed histone modifications in oxidative stress pathways in aorta macrophages in mice exposed to IH [64].…”
Section: Osahs and Histone Modificationsmentioning
confidence: 99%
“…The epigenetic modification mechanisms mainly include DNA methylation, histone tail modification, and non-coding RNA regulation, all of which modulate gene expression without changing the DNA sequence [20][21][22]. DNA hypermethylation is generally associated with gene silencing [23,24].…”
Section: Introductionmentioning
confidence: 99%